Analisis Penerapan Sistem Manajemen Pergudangan Pada Perusahaan Pt. Pertamina Dppu Ngurah Rai - Bungaran Adi Prama; Satria Akbar Gumilang; Fakhri Najmuddin; Raissa Siti Sahara (Peneliti.net, 2023)
Warehouse management is concerned with the movement, picking, packing and storage of stock in the warehouse. The existence of a warehousing management system is basically to handle and control the material in the warehouse. This writing aims to determine the effectiveness and efficiency of implementing Werehouse Management System. This study used the literature study method, where the authors used data obtained from previous research at PT. Pertamina DPPU Ngurah Rai. This study shows that implementing a Werehouse Management System can increase time efficiency and convenience for employees of PT. Pertamina DPPU Ngurah Rai to input goods in or out easily